Functional Patterns of Lexical Bundles and Limitations in Academic Writing by Thai L2 English Learners - Attapol Khamkhien (Yayasan Visi Intan Permata, 2021)
Lexical bundles, which serve as markers of fluent and appropriate language use, are referred to as